Pros and Cons of Denosumab Treatment for Osteoporosis and Implication for RANKL Aptamer Therapy - Zhang, Ning; Zhang, Zong-Kang; Yu, Yuanyuan; Zhuo, Zhenjian; Zhang, Ge; Zhang, Bao-Ting (Frontiers in Cell and Developmental Biology, 2020)
Osteoporosis is age-related deterioration in bone mass and micro-architecture. Denosumab is a novel human monoclonal antibody for osteoporosis. It is a receptor activator of nuclear factor-κB ligand (RANKL) inhibitor, which binds to and inhibits osteoblast-produced RANKL, in turn reduces the binding between RANKL and osteoclast receptor RANK, therefore decreases osteoclast-mediated bone resorption and turnover. However, adverse events have also been reported after denosumab treatment, including skin eczema, flatulence, cellulitis and osteonecrosis of the jaw. Extensive researches on the mechanism of adverse reactions caused by denosumab have been conducted and may provide new insights into developing new RANKL inhibitors that achieve better specificity and safety. Aptamers are single-stranded oligonucleotides that can bind to target molecules with high specificity and affinity. They are screened from large single-stranded synthetic oligonucleotides and enriched by a technology named SELEX (systematic evolution of ligands by exponential enrichment). With extra advantages such as high stability, low immunogenicity and easy production over antibodies, aptamers are hypothesized to be promising candidates for therapeutic drugs targeting RANKL to counteract osteoporosis. In this review, we focus on the pros and cons of denosumab treatment in osteoporosis and the implication for novel aptamer treatment.